Whispers in a bottle: the language of liquor and the politics of prohibition in nineteenth-century New Zealand. Issue 1 (2nd January 2016) - Gray, Taylor
Abstract : In 1835, in the Hokianga region of New Zealand, missionary William White and Additional British Resident Thomas McDonnell spearheaded the introduction of a prohibition on spirits. Predating British rule, the resolutions on prohibition were termed 'native law'. McDonnell's cooperation with White, a known rival, is unusual. I suggest that the key to understanding this cooperation lies in McDonnell's history as a maritime captain. British ships in the South Pacific operated within a legal vacuum in terms of the management of crew behaviour. Alcohol maintained order and, accordingly, became a symbol of power. The lawless environment aboard ships bore similarities with pre-1840 New Zealand, allowing McDonnell to exploit his knowledge of traditional maritime power plays. Consideration the Hokianga prohibition resolutions in this context illuminates both the development of this early example of New Zealand law-making, as well the ways in which settlers established control in the absence of British law.